2012
DOI: 10.1111/j.1477-9552.2012.00369.x
|View full text |Cite
|
Sign up to set email alerts
|

Sources of Firm Performance Differences in the US Food Economy

Abstract: Researchers in economics and strategy have long been interested in understanding the determinants of firm performance. We apply the relatively novel approach of hierarchical linear modelling (HLM) to a large panel of food economy firms to shed new light on the long‐standing debate about the relative importance of industry, corporate parent and business unit effects on firm profits. Our results suggest that business unit and corporate effects are more relevant than industry effects in explaining firm performanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

11
77
0
7

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(95 citation statements)
references
References 40 publications
(121 reference statements)
11
77
0
7
Order By: Relevance
“…The findings suggest a positive relationship between firm size with return on assets (ROA) [7,12], return on equity (ROE), and return on investment (ROI) [12] and based in arguments like greater resources and market opportunities of large firms, which enables to be more efficient in the use of inputs, to benefit from economies of scale and to a stronger market power. However, other studies [13] reported a negative relation, showing that smaller firms can obtain a better financial performance.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The findings suggest a positive relationship between firm size with return on assets (ROA) [7,12], return on equity (ROE), and return on investment (ROI) [12] and based in arguments like greater resources and market opportunities of large firms, which enables to be more efficient in the use of inputs, to benefit from economies of scale and to a stronger market power. However, other studies [13] reported a negative relation, showing that smaller firms can obtain a better financial performance.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies on the agrifood sector conclude that there is a direct relation between firm size and financial performance in the food industry [e.g., 7,12]. The findings suggest a positive relationship between firm size with return on assets (ROA) [7,12], return on equity (ROE), and return on investment (ROI) [12] and based in arguments like greater resources and market opportunities of large firms, which enables to be more efficient in the use of inputs, to benefit from economies of scale and to a stronger market power.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Traill (1997) examined the effects of the globalization on the supply and the quality for food industries. Chaddad and Mondelli (2013) identified that the specific strategies of firms have effects on the firms' performance in the food industry.However, the literature related to the food security seldom takes substitutability into consideration. As we know, there exists a high degree of product substitutability in the food industry, while food producers are always asymmetric.…”
mentioning
confidence: 99%
“…Traill (1997) examined the effects of the globalization on the supply and the quality for food industries. Chaddad and Mondelli (2013) identified that the specific strategies of firms have effects on the firms' performance in the food industry.…”
mentioning
confidence: 99%